2008
DOI: 10.1007/s00384-007-0427-3
|View full text |Cite
|
Sign up to set email alerts
|

NOTES—case report of a unidirectional flexible appendectomy

Abstract: In the space of a year, the first operations have been performed on human subjects by a few select work groups. NOTES procedures are still in the initial stages of clinical development. Until they can be introduced into surgical daily routine, further improvements are required as to equipment, technology and operative procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
9

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(60 citation statements)
references
References 14 publications
0
51
0
9
Order By: Relevance
“…Most NOTES procedures have been hybrid procedures requiring at least one transabdominal port and the most common procedures are cholecystectomy, appendicectomy and mainly performed via transvaginal access. Thus far, pure transvaginal NOTES have been performed in cholecystectomies, 17,18 appendectomies 19,20 and nephrectomy. 21 Only a few of the studies reported pure transvaginal NOTES procedures in gynecological surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Most NOTES procedures have been hybrid procedures requiring at least one transabdominal port and the most common procedures are cholecystectomy, appendicectomy and mainly performed via transvaginal access. Thus far, pure transvaginal NOTES have been performed in cholecystectomies, 17,18 appendectomies 19,20 and nephrectomy. 21 Only a few of the studies reported pure transvaginal NOTES procedures in gynecological surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Many attempts have been made to reduce complications by minimizing the number of trocars inserted and reducing the size of incisions, and have been applied to cholecystectomy, appendectomy and splenectomy using single port laparoscopic surgery (SPLS) [7][8][9]. SPLS has also been used to perform hysterectomies, with acceptable clinical safety [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Die Entwicklung von NOTES ist in der letzten Zeit rasant verlaufen, so wur den bereits Splenektomien, Cholezystek tomien, Appendektomien, Pankreasre sektionen, Nephrektomien und Darmre sektionen durchgeführt, wobei sich viele Verfahren noch in der tierexperimentel len Phase befinden [6,8,9,10]. …”
unclassified